Determinan Pengelolaan Keuangan Dana Desa - Eni Dwi Susliyanti (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2020)
This study aims to analyze factors that influencing Village Fund Financial Management in Sleman Regency. Independent variables that used in this study are Good Corporate Governance principles which consist of: Transparency, Accountability, Independence, Fairness, Implementation of Village Government, and Community Empowerment. Meanwhile dependent variable is village fund financial management. Population of this study are 43 districts from 11 sub-districts where located in Sleman Regency. Samples from this research is village officials which consisted of 150 respondents. The results of the study indicate that when tested partially, the principle of transparency and accountability influences the management of village financial funds in Sleman Regency. However, other variables did not affect the financial management of village funds in Sleman Regency. If tested simultaneously, the results show that there is an influence on the financial management of village funds in Sleman Regency.